The Effect of Animation Video-Based Education Toward Stunting Knowledge and Attitude Among Female Adolescents in Jakarta - Donana, Yurongki; Nurhayati, Nurhayati; Endah P, Tria Astika; Hadiyani, Wini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The prevalence of stunting in Indonesia is one of the crucial problems that will have an impact on the next generation, so it needs to be prevented. Increasing stunting prevention knowledge and attitudes in adolescents related to health investment in the first 8000 days of life is important in reducing stunting rates. The aims of the study to identify the effect of investment education for the first 8000 days of life with animated videos as an effort to break the stunting cycle. Methods: This study used the Quasi Experiment method with a two-group pre-posttest design with 214 respondents divided into an intervention group and a control group with 107 people in each group. The research analysis used Wilcoxon Rank and Manova. Results: This study after being given the intervention showed that there were significant differences in the knowledge and attitude scores between the control group and the intervention group with a p-value of 0.000 (p <α 0.05). Conclusion: This study shows that providing education on health investment in the first 8000 days of life with animated videos affects increasing knowledge and attitudes of young women in preventing stunting.